Peripheral Precocious Puberty In A Four Years Old Boy With Classic Simple Virilizing Congenital Adrenal Hyperplasia - Natal Ria; I Wayan Bikin Suryawan; I Made Arimbawa; I Made Darma Yuda (Asian Journal of Social and Humanities, 2023)
The study aims to describe a case of precocious puberty caused by classic simple virilizing congenital adrenal hyperplasia. This is a case of 4 years-old boy who developed premature pubarche 5 month before consultation. Patient also has penis enlargement with prepubertal testes and facial acne since age of three. His voice also changed to be more like an adult male voice. Physical examination revealed an alert boy, with normal vital sign, body weight of 27 kilograms (>P95, CDC Growth Chart 2000) and height of 126 centimeter (>P95, CDC Growth Chart 2000), with advanced bone age of 14-years-old child. The Sexual Maturity Rating score was G1P3( tanner stage 3), and his height was more than his mid-parenteral height. Laboratory test  was done revealed 17-OHP of 196.03 ng/ml (n: <= 0.90ng/ml), high level of testosterone at 270.1 ng/ml (n: <= 0.19ng/ml), level of B-HCG : <2.3mIU/ml, low level of LH : 0.1 mIU/ml (n: >0.6 mIU/ml), and low level of  FSH: 0.1 mIU/ml (n: 0-5.0mIU/ml). Ultrasound of Kidney shows a picture of hyperplasia of left adrenal gland. All of these findings allowed diagnosing him with classic simple virilizing congenital adrenal hyperplasia. Based on this diagnosis, he was then started on hydrocortisone, and after 6 months of starting the treatment, he has a favourable clinical outcome, without any secondary sex characteristics or bone age progression. Peripheral precocious puberty due to classic simple virilizing congenital adrenal hyperplasia may be asymptomatic from birth to the preschool age, therefore early  detection, immediate and appropriate managements are crucial and important to prevent late outcomes.